Modeling the System of Economic Security of AgroHoldings as the Basis for their Sustainable Development in the Context of Global Crisis Management - A. V. Gluschchenko; E. P. Kucherova; M. V. Denisov (Учёт. Анализ. Аудит, 2018)
The global economic system is at the stage of its active formation and development. Its borders and conditions of existence are constantly changing, which is accompanied by crises, which affect the economic systems of all countries participating in the world economy. The current global fnancial crisis, which is global and systemic, revealed a lack of effective theoretical approaches to the development of practical methods for overcoming the crisis phenomena used in the management of integrated agro-formations. This predetermines the need to improve the system of global crisis management that contributes to an adequate response to crises and is based on innovative approaches and the application of modern concepts of sustainable development in order to ensure economic security. The globalization of the fnancial and food markets, on the one hand, allows the agro-holdings to compare and evaluate the effciency of investment simultaneously within the entire international economy; expand and strengthen the fnancing capacity of various economic projects. On the other hand, qualitative changes in the global economy are of a deep and risky nature, due to the rapid development of fnancial innovations, which leads to an insuffcient degree of development of the system of ensuring economic security of international activities of economic entities. As a result of the analysis of the activities of integrated agro-formations, the current trends in the development and functioning of agricultural holdings in the context of the global fnancial crisis have been revealed. The specifcs of ensuring sustainable development of agrostructures in the context of global crisis management are defned: soil-climatic, biological, ecological, technological, and organization of agricultural territories. A model for ensuring the economic security of the agricultural holding through a sustainable development strategy was developed and justifed, including the following elements: a mission, a goal and a system of balanced indicators. The decomposition of the activities of integrated agro-formation into groups of balanced indicators has been made: fnance, customers, internal business processes, training and development, competitors and on-farm decomposition system. The internal and external threats to economic security, which are the basis for the selected groups of the BSS (balanced scorecard system) for integrated agro-formations, are singled out. Fields of economic security of the agro-structure (critical, low, normal and high) are defned, as well as sustainable development strategies for each feld, allowing to move from a critical level of economic security to the high one.